Analisis Semantik Leksikal Pada Pantun Daerah Masyarakat di Kecamatan Kelam Tengah Kabupaten Kaur - Tandayu, Ario; Zasrianita, Fera; Sari, Wenny Aulia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This study aims to analyze the lexical semantics in traditional rhymes (pantun) of the community in Kelam Tengah District, Kaur Regency. Pantun is a form of ancient literature that is still preserved in Indonesia, particularly in Kelam Tengah District. It contains both explicit and implicit meanings that need to be explored in depth to understand the local wisdom embedded within. Lexical semantic analysis is employed to comprehend the meanings of words in these rhymes. The research utilizes a qualitative method with a descriptive approach. The data sources are local pantun collected through observation, interviews, and documentation. The data analysis techniques include data reduction, data presentation, and conclusion drawing. The results show that various lexical meanings are found within the pantun of Kelam Tengah, conveying messages to readers and listeners. These rhymes reflect aspects of the local community's life, including religious, moral, social, and cultural values. Additionally, pantun serves as a medium for communication, emotional expression, and education for the people in Kelam Tengah. In conclusion, the pantun of Kelam Tengah reflects the community's cultural richness, daily life, and moral values, such as the importance of education, discipline, and adherence to local traditions. Beyond entertainment, these rhymes function as a medium for transmitting wisdom, advice, and aspirations passed down through generations. Keywords: Kelam Tengah Community, Local Rhymes, Lexical Semantics